2019
DOI: 10.1039/c9ra03359a
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of novel phenylaminopyrimidines with antiproliferative activity against colorectal cancer

Abstract: A new series of phenylaminopyrimidine (PAP) derivatives was designed and synthesized to act against tyrosine kinases for the treatment of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The results explained that compound 30 was highly selective towards the Src kinase enzyme with EC 50 of 1.3 μM. This derivative showed hydrogen bond interactions with Gln278, Lys298, and Thr341 amino acids and steric interaction with Met344 and Ile339 residue of Src kinase [38] …”
Section: Recent Development Of Src Kinase Inhibitorsmentioning
confidence: 90%
See 1 more Smart Citation
“…The results explained that compound 30 was highly selective towards the Src kinase enzyme with EC 50 of 1.3 μM. This derivative showed hydrogen bond interactions with Gln278, Lys298, and Thr341 amino acids and steric interaction with Met344 and Ile339 residue of Src kinase [38] …”
Section: Recent Development Of Src Kinase Inhibitorsmentioning
confidence: 90%
“…This derivative showed hydrogen bond interactions with Gln278, Lys298, and Thr341 amino acids and steric interaction with Met344 and Ile339 residue of Src kinase. [38] Schoene et al designed and synthesized 2H-Indazoles candidates. These candidates had been screened as inhibitors of Src, Tie2 and SGK1.…”
Section: Recent Development Of Src Kinase Inhibitorsmentioning
confidence: 99%
“…Asciminib is a potent and selective allosteric ABL1 [20,21] inhibitor patented by Novartis Oncology [6,8] . Asciminib exhibited reduction in the side effects as compared to another TKI drug [10,23] basutinib. Various other approved CML drugs [11,12] have been discontinued after four years in use for cancer [7–9,19] treatment due to the problem of resistance which has arisen due to point mutations in BCR‐ABL [2,4,8,15,21] .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Phenyl amino pyrimidine and hydroxysubstituted phenyl amino pyrimidine showed a selective src kinase inhibitory response and excellent anticancer response against the HT29CRC and HCT-116 cell lines. 16 Mohammed et al reported on in vitro anti-proliferative studies of trimethoxy phenyl-substituted pyridine against the MCF7, HEPG-2 and HCT116 cancer cell lines. 4-Nitro-substituted trimethoxy phenyl pyridine showed a signicant anticancer response against the HCT116, HEPG-2 and MCF7 cancer cell lines compared with hydroxy-, methoxy-, methyl-substituted and chloro trimethoxy phenyl pyridine.…”
Section: Introductionmentioning
confidence: 99%